2013
DOI: 10.1111/ppe.12058
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Cognitive Ability in Early Childhood: a Population‐based Cohort Study

Abstract: Cognitive ability is related to the entire range of gestational age, including children born at 34-36 and 37-38 weeks gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 32 publications
6
108
3
2
Order By: Relevance
“…This association was not seen at 24 months, which is consistent with results from some studies 14,26 but differs from other studies. 27,28 At preschool and kindergarten timepoints, similar to previous studies of late preterm infants at preschool and early school age, 10,11 we found that late preterm infants demonstrate less optimal early reading skills in preschool and kindergarten and less optimal 5 All analyses adjusted for maternal age, maternal race or ethnicity, socioeconomic status at 9 mo, parenting, infant gender, birth weight, and receipt of early intervention services. Analyses at preschool and kindergarten also included age at assessment and month of school.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This association was not seen at 24 months, which is consistent with results from some studies 14,26 but differs from other studies. 27,28 At preschool and kindergarten timepoints, similar to previous studies of late preterm infants at preschool and early school age, 10,11 we found that late preterm infants demonstrate less optimal early reading skills in preschool and kindergarten and less optimal 5 All analyses adjusted for maternal age, maternal race or ethnicity, socioeconomic status at 9 mo, parenting, infant gender, birth weight, and receipt of early intervention services. Analyses at preschool and kindergarten also included age at assessment and month of school.…”
Section: Discussionsupporting
confidence: 68%
“…7 -9 Recent studies have examined the possibility of a dose-response association between gestational age and early school performance by comparing early school outcomes of late preterm infants with outcomes of children born at early term (37-38 weeks) and term gestation (39-41 weeks). 10 -12 Compared with children born at early term and term gestation, children born in the late preterm period demonstrate poorer performance on tests of early school readiness, spatial abilities, and verbal reasoning in early childhood, 10 poorer educational achievement at age 5, 11 and poorer school performance at age 7. 12 Despite these findings, little is known about the pattern of development in late preterm infants in the period before school entry.…”
mentioning
confidence: 99%
“…Improvements in medical care or in the educational system over the years may have resulted in better outcomes among early-term individuals. However, findings regarding early-term birth and learning abilities in more recent cohorts are mixed (MacKay, Smith, Dobbie, & Pell, 2010;Poulsen et al, 2013;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is associated with low intelligence (Jaekel, Baumann, & Wolke, 2013;Kerr-Wilson, Mackay, Smith, & Pell, 2012) and learning difficulties in several domains, including reading and spelling (Poulsen et al, 2013;Schneider, Wolke, Schlagmuller, & Meyer, 2004). Problems with mathematics have been found to be especially common in preterm children (Simms et al, 2014) and are associated with global cognitive deficits (Jaekel & Wolke, 2014; Simms et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…22,26,27,[29][30][31][32][33][34][35][36] The literature is not entirely consistent: some studies have found no differences in neurocognitive performance between those born late preterm and term. 30 4 We also excluded 30 participants with a history of stroke, 6 with Parkinson's disease, and 1 who discontinued the CERAD-NB (n = 37 [3.3%] …”
Section: What This Study Addsmentioning
confidence: 99%